TINJAUAN YURIDIS NILAI PESANGON PERUSAHAAN MELAKUKAN EFISIENSI SETELAH DI BERLAKUKANNYA UNDANG-UNDANG CIPTA KERJA NO. 6 TAHUN 2023 - Ristio; Diding Rahmat (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
Currently, the formation of the normative level of labor law in Indonesia is again undergoing significant changes after the Government Regulation in Replacement of the Job Creation Law Number 2 of 2022 which has been passed into the Job Creation Law Number 6 of 2023. One aspect that has undergone changes is the provision of severance pay to employees who are terminated (PHK) as a result of the company carrying out efficiency before and after the enactment of the Job Creation Law Number 6 of 2023 (UUCK). The focus of this research is positive legal norms of legislation, through normative legal research methods. The results of this research show that workers in Indonesia must receive severance pay after being laid off because companies carry out efficiency as previously regulated through Article 167 paragraph (1) of Employment Law No. 13 of 2003 (UUK), some have even regulated it in a collective agreement agreed upon by workers through the trade union and employer. which is then regulated in the UUCK where the nominal severance pay arrangements are different from those regulated in the UUK.